The impacts of the tourism sector on the ecoefficiency of the Latin America and Caribbean countries - Castilho, Daniela dos Reis (2020)
This paper examines the impacts of the tourism sector on the overall eco-efficiency of 22 Latin America and Caribbean countries from 1995 to 2016. A two-stage Data Envelopment Analysis methodology was used in order to first calculate the overall eco-efficiency of the countries from the sample (considering the CO2 emissions as the input and the economic growth as the output), with the outcomes pointing to an eco-efficiency decrease in the majority of countries. Posteriorly, a Panel Autoregressive Distributed Lag model was applied to analyse the impacts of tourism arrivals, tourism capital investment, and direct tourism contribution to employment on the previously calculated overall eco-efficiency. Moreover, given the presence of cross-sectional dependence, heteroscedasticity, and first order autocorrelation in the model, the Driscoll-Kraay estimator was used, and the results indicate that tourism arrivals, use of nonrenewables to generate (a substantial part of) electric power to consumption, and trade openness contributed to the decrease in these countries' eco-efficiency, both in the short- and long-run. Contrariwise, tourism capital investment, direct tourism contribution to employment, and Human Development Index seem to promote eco-efficiency in the long-run. These findings suggest that policymakers should pay attention to these destinations carrying capacity given that, if they ignore this feature, it can produce environmental and climatic shocks to these countries, as well as bringing constraints to their development (both in the short- and long-run). Simultaneously, in order to grant their sustainable development, they must continue to encourage investments in sustainable tourism projects and productive employment to all. Lastly, we see that the error correction mechanism has a negative and statistically significant value in the estimation, which points to the existence of a cointegration/long memory relationship between our variables.